Healthcare: A touch of good health - McKay, Michael; Douglas, Gerald (Technical Centre for Agricultural and Rural Cooperation, 2009)
A locally developed touchscreen computer system helps to guide staff in rural health centres in Malawi through diagnosis and treatment procedures.